Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $f(x,y) = 1$ if $0 < y <2x$, $0 < x < 1$ and zero otherwise. Find

(a) $f(y |x)$

(b) $E[Y|x]$

(c) $\rho$

Note that $\rho$ is the correlation constant.

In my book the only formula for the correlation constant is $\rho = \dfrac{\sigma_{xy}}{\sigma_x \sigma_y}$ where $\sigma_{xy}$ is the covariance of a pair of random variables X and Y and $\sigma_x = \sqrt{Var(X)}$ and $\sigma_y =\sqrt{Var(Y)}$ are the variance of random variable X and Y respectively.

I've calculated all of them but (c) because there were a lot of calculation and apparently it might be a question on a 50-minute midterm

(a) $f(y|x) = \frac{1}{2x}$

(b) $E[Y|x] = x$

(c) Textbook answer was $1/2$

share|improve this question
1  
No, $\sigma_x$ and $\sigma_y$ must be the standard deviations of $X$ and $Y$. –  Robert Israel Nov 9 '12 at 3:44
    
@RobertIsrael, oh yes oops. –  jip Nov 9 '12 at 4:03

2 Answers 2

up vote 1 down vote accepted

(a) $$f_{Y|X}(y|x) = \frac{f(x,y)}{f_X(x)} = \frac{f(x,y)}{\int_{-\infty}^\infty f(x,t)\ dt}$$ For $0 < x < 1$ we have $f_X(x) = \int_0^{2x} 1\; dt = 2x$, while $f_X(x) = 0$ otherwise. Thus $f_{Y|X}(y|x) = \frac{1}{2x}$ for $0 < y < 2x$ and $0 < x < 1$ (it's wrong to just say $f_{Y|X}(y|x) = 1/(2x)$ without specifying the region of the $xy$ plane for this); $f_{Y|X}(y|x) = 0$ if $0 < x < 1$ and either $y < 0$ or $y > 2x$; $f_{Y|X}(y|x)$ is undefined if $x \le 0$ or $x \ge 1$.

(b) $E[Y|X=x] = \int_{-\infty}^{\infty} y f_{Y|X}(y|x)\ dy$. For $0 < x < 1$ this is $\int_0^{2x} \dfrac{y}{2x}\ dy = x$. Again, for $x \le 0$ or $x \ge 1$ it is undefined.

(c) $E[X] = \int_{-\infty}^\infty x f_X(x)\ dx = \int_0^1 2 x^2\ dx = 2/3$

Similarly, $E[X^2] = \int_0^1 2 x^3\ dx = 1/2$. Thus $\sigma_X^2 = E[X^2] - E[X]^2 = 1/18$.

$E[Y] = E[E[Y|X]] = E[X] = 2/3$

For $0 < x < 1$, $E[Y^2 | X=x] = \int_0^{2x} \dfrac{y^2}{2x}\ dy = \dfrac{4x^2}{3}$ so $E[Y^2] = E[E[Y^2|X]] = E[4 X^2/3] = (4/3) E[X^2] = 2/3$. Thus $\sigma_Y^2 = E[Y^2] - E[Y]^2 = 2/9$.

$E[XY] = E[X E[Y|X]] = E[X^2] = 1/2$ so $\text{Cov}(X,Y) = E[XY] - E[X] E[Y] = 1/18$.

Finally, $\rho = \dfrac{\text{Cov}(X,Y)}{\sigma_X \sigma_Y} = \dfrac{1}{2}$

share|improve this answer

If you have learned how to visualize the concept of conditional densities, the answer to part (c) (and indeed parts (a) and (b) as well) can be obtained with a little bit visualization and hardly any calculation. I will explain below, but it takes longer to write down than to simply draw a simple sketch and deduce the answers. A picture is indeed worth the next thousand words!

The joint density can be thought of as a right prism of height $1$ with triangular base sitting on the $x$-$y$ plane. The base has vertices are $(0,0)$, $(1,0)$ and $(1,2)$, and thus area $1$. The conditional density of $Y$ given that $X$ has taken on value $x$ is proportional to the cross-section of this prism by the plane at $x$. For $0 < x < 1$, this cross-section is a rectangle with base of length $2x$, and so the conditional density of $Y$ is a uniform density $U(0,2x)$, that is, $$f_{Y\mid X}(y\mid X=x) = \begin{cases}\frac{1}{2x}, & 0 \leq y \leq 2x,\\ & \\ 0, & \text{otherwise.}\end{cases}$$ Since the conditional density is uniform on $(0,2x)$, it follows immediately that $E[Y \mid X=x] = x$.

Turning to the matter of calculating $\rho$, note that by very similar visualization, the conditional density of $X$ given $Y = y$ is a uniform density on $(y/2, 1)$ and thus $E[X \mid Y = y] = 1/2 + y/4$, the midpoint of the base of the uniform density.

Now, $E[Y\mid X = x]$ and $E[X\mid Y = y]$ are the minimum-mean-square-error (MMSE) estimators for $Y$ and $X$ respectively given the value of the other random variable, and since these are linear functions, they are also the MMSE linear estimators for $Y$ and $X$ respectively. Now, the MMSE linear estimators are lines through the mean point $(\mu_X,\mu_Y)$ given by $$\begin{align*} \frac{y-\mu_Y}{\sigma_Y} &= \rho\frac{x-\mu_X}{\sigma_X}\qquad \equiv \quad y = x\\ \frac{x-\mu_X}{\sigma_X} &= \rho \frac{y-\mu_Y}{\sigma_Y} \qquad \equiv \quad x = \frac{1}{2}+\frac{y}{4} \end{align*}$$ Clearing fractions, we see that $\rho\frac{\sigma_Y}{\sigma_X} = 1$ and $\rho\frac{\sigma_X}{\sigma_Y} = \frac{1}{4}$, giving $\rho^2 = \frac{1}{4}$ and $\rho=\frac{1}{2}$. (The solution $\rho = -\frac{1}{2}$ can be discarded since we know that $\rho$ is positive.)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.